Fruit-derived polyphenol supplementation for athlete recovery and performance - Bowtell, J.; Kelly, V. (Sports Medicine, 2019)
Polyphenols are characterised structurally by two or more hydroxyl groups attached to one or more benzene rings, and provide the taste and colour characteristics of fruits and vegetables. They are radical scavengers and metal chelators, but due to their low concentration in biological fluids in vivo their antioxidant properties seem to be related to enhanced endogenous antioxidant capacity induced via signalling through the Nrf2 pathway. Polyphenols also seem to possess anti-inflammatory properties and have been shown to enhance vascular function via nitric oxide-mediated mechanisms. As a consequence, there is a rationale for supplementation with fruit-derived polyphenols both to enhance exercise performance, since excess reactive oxygen species generation has been implicated in fatigue development, and to enhance recovery from muscle damage induced by intensive exercise due to the involvement of inflammation and oxidative damage within muscle. Current evidence would suggest that acute supplementation with ~ 300 mg polyphenols 1-2 h prior to exercise may enhance exercise capacity and/or performance during endurance and repeated sprint exercise via antioxidant and vascular mechanisms. However, only a small number of studies have been performed to date, some with methodological limitations, and more research is needed to confirm these findings. A larger body of evidence suggests that supplementation with > 1000 mg polyphenols per day for 3 or more days prior to and following exercise will enhance recovery following muscle damage via antioxidant and anti-inflammatory mechanisms. The many remaining unanswered questions within the field of polyphenol research and exercise performance and recovery are highlighted within this review article.